The Influence of Pricing Attractiveness, Price Sensitivity, and Product Variety on Consumers' Purchase Intention: An Analysis of Nepal’s Footwear Market - Rai, Arjun; Bhattarai, Mandip (Journal of Management, 2023)
This study examined the impact of Pricing Attractiveness, Price Sensitivity, and Product Variety on Purchase Intention in the context of Nepali brand footwear in Nepal. The analysis was based on data collected from a sample of 248 respondents. Cronbach's alpha values were calculated for the items, indicating a high level of internal consistency for the overall set of items. Cronbach's alpha values for all the constructs, such as Pricing Attractiveness, Price Sensitivity, Purchase Intention, and Product Variety, were found to be acceptable. To examine the impact of explanatory variables on the dependent variable, a Linear Regression Model was used. The results revealed that all three predictor variables significantly influenced Purchase Intention. The overall model exhibited a good fit, explaining 33.1% of the variance in Purchase Intention. In conclusion, the study provides strong evidence for the internal consistency and reliability of the items used in measuring various constructs. Moreover, it highlights the importance of Pricing Attractiveness, Price Sensitivity, and Product Variety in influencing consumers' Purchase Intention. The findings contribute valuable insights for researchers and practitioners alike, offering potential avenues for the development of effective strategies to enhance consumer behavior and decision-making in relevant domains.